2012
DOI: 10.1007/s12038-011-9176-0
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: A double-edged sword in Alzheimer’s disease

Abstract: Autophagy is a major protein degradation pathway that is essential for stress-induced and constitutive protein turnover. Accumulated evidence has demonstrated that amyloid-beta (A beta) protein can be generated in autophagic vacuoles, promoting its extracellular deposition in neuritic plaques as the pathological hallmark of Alzheimer's disease (AD). The molecular machinery for A beta generation, including APP, APP-C99 and beta-/gamma-secretases, are all enriched in autophagic vacuoles. The induction of autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 77 publications
3
61
0
Order By: Relevance
“…Autophagy is a lysosome-directed vesicular trafficking pathway and a major degradation pathway of intracellular components that is essential for survival and adaptation to nutrient elimination (37). Autophagy also plays a role in maintenance of neuronal cells and has been implicated in clearance of pathogens and antigen presentation (38), including the clearance of amyloid ␤ protein from neuronal cells (39). LC3I is converted to LC3II by lipidation during autophagy.…”
Section: Modeling the Effect Of Diabetes On Neurons By Cholesterol Dementioning
confidence: 99%
“…Autophagy is a lysosome-directed vesicular trafficking pathway and a major degradation pathway of intracellular components that is essential for survival and adaptation to nutrient elimination (37). Autophagy also plays a role in maintenance of neuronal cells and has been implicated in clearance of pathogens and antigen presentation (38), including the clearance of amyloid ␤ protein from neuronal cells (39). LC3I is converted to LC3II by lipidation during autophagy.…”
Section: Modeling the Effect Of Diabetes On Neurons By Cholesterol Dementioning
confidence: 99%
“…Ras GTPase activation mediates EGF-induced stimulation of γ-secretase to increase the nuclear function of the APP intracellular domain (AICD) (11). Consistent with the role of EGF signaling in AD, the intracellular mediators downstream of EGF signaling (which include Grb2, ShcA, and Abl) directly or indirectly interact with APP (12); these findings support the correlation between EGFR/ ErbB-dependent signaling and AD susceptibility.Autophagy controls the clearance of misfolded proteins and damaged organelles, and plays an essential role in maintaining neuronal functions (13,14). Previous studies have demonstrated that autophagy is instrumental to the clearance of proteins related to neurodegenerative diseases; these proteins include polyglutamine aggregates in Huntington's disease, Lewy body-like α-synuclein aggregates in Parkinson's disease, and neurofibrillary tangles in AD (15-18).…”
mentioning
confidence: 99%
“…Autophagy controls the clearance of misfolded proteins and damaged organelles, and plays an essential role in maintaining neuronal functions (13,14). Previous studies have demonstrated that autophagy is instrumental to the clearance of proteins related to neurodegenerative diseases; these proteins include polyglutamine aggregates in Huntington's disease, Lewy body-like α-synuclein aggregates in Parkinson's disease, and neurofibrillary tangles in AD (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Briefly, 2x10 6 cells from different groups were washed with PBS, stained with Annexin V-FITC and PI for 15 min in the dark at room temperature. Then samples (10,000 cells/sample) were analyzed using a flow cytometer (BD Accuri C6; BD Biosciences, San Jose, CA, USA).…”
Section: Flow Cytometry For Cell Apoptosis Analysismentioning
confidence: 99%
“…Increasing evidence has suggested that autophagy is a double-edged sword in AD development (6). Although a great deal of research has demonstrated that autophagy has a beneficial effect against AD (7)(8)(9), abnormalities of autophagy may also be a major risk factor for AD (10).…”
Section: Introductionmentioning
confidence: 99%